2020
DOI: 10.1183/13993003.01610-2020
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of memantine in the prevention and treatment of COVID-19: its antagonism of nicotinic acetylcholine receptors and beyond

Abstract: Recently, LEUNG et al. [1] proposed that α7-subtype nicotinic acetylcholine receptor (α7-nAChR) antagonists might decrease angiotensin-converting enzyme (ACE)2 receptor expression in respiratory epithelium and, hence, prevent severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) invasion of pulmonary epithelial cells. Let us further theoretically evaluate this assertion and contribute to the quest for potential medications that might reduce virulence and pathogenicity of coronavirus disease 2019 (COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 10 publications
0
16
0
2
Order By: Relevance
“…More recent studies support the antiviral potential of aminoadamantanes, including development of novel compounds (Kesel et al 2013 ) and treatment of virus replication (Leibowitz and Reneker 1993 ) including HCoV-OC43 replication by memantine (Brison et al 2014 ). Most recently, Hasanagic and Serdarevic ( 2020 ) suggested that memantine (besides its NMDA-R channel blocking properties) through its α7-nAChR antagonism may counteract proinflammatory cytokines induced in cell cultures by HCoV-OC43. This is of special interest, because α7-nAChR is localized in lungs and in the CNS.…”
Section: Implications For Neurodegenerative Disordersmentioning
confidence: 99%
“…More recent studies support the antiviral potential of aminoadamantanes, including development of novel compounds (Kesel et al 2013 ) and treatment of virus replication (Leibowitz and Reneker 1993 ) including HCoV-OC43 replication by memantine (Brison et al 2014 ). Most recently, Hasanagic and Serdarevic ( 2020 ) suggested that memantine (besides its NMDA-R channel blocking properties) through its α7-nAChR antagonism may counteract proinflammatory cytokines induced in cell cultures by HCoV-OC43. This is of special interest, because α7-nAChR is localized in lungs and in the CNS.…”
Section: Implications For Neurodegenerative Disordersmentioning
confidence: 99%
“…Against excessive extracellular glutamate accumulation triggered by diverse inflammatory and oxidative processes, memantine protects cells from glutamate excitotoxicity by blocking the extrasynaptic NMDA receptors [ 57 ]. Since memantine, is an antagonist of NMDA receptors, it diminishes the SARS-CoV-2-related oxidative stress and inflammation in neurons [ 58 ].…”
Section: Functions Of Receptors In Brain Invasion Of Sars-cov-2mentioning
confidence: 99%
“…Therefore, it is likely that antagonists of α7-nAChR could have the potential, by virtue of their ability to decrease ACE2 receptor expression in respiratory epithelium and prevent SARS-CoV-2 invasion of pulmonary epithelial cells. Searches for such agents are currently ongoing and, interestingly, memantine, in addition to its well-established action as a non-competitive antagonist of NMDA receptors, is a very potent antagonist of α7-nAChR [30]. It also exerts protective anti-inflammatory effects by suppression of cytokine expression as shown in an experimental model of lung injury [31].…”
Section: The Nicotinic Cholinergic Receptor and Covid-19mentioning
confidence: 99%